Control of illegal domestic building extension by local authority / Zamizi Zakaria - Zakaria, Zamizi (2004)
Building extension is included in part of building alteration work. Nowadays, people who own a building especially terrace and bungalow house prefer to extend their buildings for extra spaces. The extension can be legal or illegal. Legal when the extension is built with obtaining permission form local authority and illegal when the extension is built without obtaining permission. The illegal condition of building extension may make the extensions built in disoriented, bad esthetic look and in dangerous condition. To control this negative situation in a municipality, local authority desires for every building extension to have obtained permission and then follow all the permission’s instructions. The failure of building owners to obtain the permission and follow the condition and instruction may make their building extension being illegal. This dissertation will study how local authority controls the building extension through permission stages and what are the enforcement steps taken to illegal extensions.